Sulfur chains glass formed by fast compression - Shi, Kaiyuan; Dong, Xiao; Zhao, Zhisheng; Su, Lei; Ji, Cheng; Li, Bing; Zhang, Jiaqing; Dong, Xingbang; Qiao, Pu; Zhang, Xin; Yang, Haotian; Yang, Guoqiang; et al. (Nature communications, 2025)
Due to the sulfur’s atoms’ propensity to form molecules and/or polymeric chains of various sizes and configuration, elemental sulfur possesses more allotropes and polymorphs than any other element at ambient conditions. This variability of the starting building blocks is partially responsible for its rich and fascinating phase diagram, with pressure and temperature changing the states of sulfur from insulating molecular rings and chains to semiconducting low- and high-density amorphous configurations to incommensurate superconducting metallic atomic phase. Here, using a fast compression technique, we demonstrate that the rapid pressurisation of liquid sulfur can effectively break the molecular ring structure, forming a glassy polymeric state of pure-chain molecules ( Am-S P ). This solid disordered chain state appears to be (meta)stable in the P-T region usually associated with phase I made up of S 8 . The elemental sulfur glass, made up from one of the simplest building blocks, offers a unique prospect to study the structure and property relationships of various other phases of sulfur and their interactions. More importantly, the fast compression technique performed at any temperature effectively like thermal quenching, opening up possibilities in high pressure synthesis by providing an effective and fast way of changing the fundamental thermodynamical parameter. Rapid pressurization of hot liquid sulfur can effectively break the molecular ring structure and form a glassy state of chain molecules. Fast compression acts as thermal quenching providing an alternative way of changing the thermodynamical parameters.